Analysis of Financial Feasibility of Farming and Vegetable Marketing StrategyHydroponics at the Jambi Hydroponics Family - Karina, Fellicia Shakita; Husin, Laila (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2022)
The objectives of this research are: (1) to describe the hydroponic cultivation method and supply network of input spply in Family Hidroponik Jambi, 2) to analyze the income and financial feasibility of hydroponic vegetable business in Family Hidroponik Jambi, 3) to describe marketing strategies that implemented by Family Hidroponik Jambi. This research was conducted at Family Hidroponik Jambi which is located at Haji Adam Malik Street, Thehok, Jambi Selatan, Jambi City. This location selection is done purposively or intentionally. Data collection was carried out in February 2022. The research method used in this study was the case study method. Sampling samples in this research were the owners of hydroponic vegetables in Family Hidroponik Jambi. The selection of samples used by purposive sampling method or intentionally with the consideration that the scale of the farm has long been established, is economical, has partners and has a fixed market, making it easier for researchers to collect the information needed during the study. Family Hidroponik Jambi was used as a source of data in preparing the financial feasibility of Family Hidroponik Jambi vegetable business. For discussion, other supporting sources and libraries are also used as references. The results showed that (1) the production inputs needed in the procurement of raw materials for the Family Hidroponik Jambi hydrponic vegetable business were seeds, rockwool and nutrients obtained from the Abadi Jaya Tani Company. Hydroponic cultivation includes preparation of planting media, seeding, planting, care and harvesting, (2) the financial feasibility of Family Hidroponik Jambi vegetable business is declared feasible to be cultivated with a projected age of 10 years based on the NPV value is Rp89.567.673, Net B/C is 1.1, Gross B/C is 1.8, Payback Periode value is 2.8, IRR is 64.8 percent which is more than the interest rate, and sensitivity analysis on sales volume if there is a decrease in the amount of vegetable production by 7.21 percent hydroponic vegetable business in Family Hydroponics Jambi is still declared feasible, (3) the hydroponic vegetable business at Family Hidroponik Jambi is implementing 5P marketing strategy that is product strategy, price strategy, promotion strategy, place strategy and participant strategy